Separation of the alkaloids of Citrus grandis - Cruz, Resurreccion I.; Santos, Rizalina B.; Concepcion. Adoracion B. (Quezon City: Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1983.)
The dried root bark of Citrus grandis was extracted with ethanol and this was partitioned between chloroform and water with the ratio of 1:3:1 (extract:water:chloroform). The chloroform layer was used for the separation of the alkaloids.
Thin layer chromatography was performed on this extract and benzene and benzene:acetone (9:1) were found to be good solvents for separation.
Column chromatography was performed and various fractions were separated. These fractions were found to contain alkaloids together with other non-alkaloidal substituents. By this column chromatography the alkaloids have been separated but not necessarily isolated.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, October 1983.
Keywords: Alkaloids; Citrus; Lukban; Suha